Examining the Thermal Comfort Characteristics of Naturally Ventilated Residential Buildings in New Zealand - Pokhrel, M; Anderson, T; Currie, J; Lie, T (Australian PV Institute, 2016)
In New Zealand’s (NZ) mild climatic conditions most residential houses are ventilated naturally, mainly by opening windows. Previous studies have found that an overwhelming proportion of housing stock performs poorly from both a thermal and health perspective and hence there is a need to better understand this. Now, analytically evaluating the thermal comfort characteristics of residential houses subject to natural ventilation is particularly challenging, as the solution is not explicit. Determining a solution requires the heat and mass transfer assessment to be driven by complex and non-linear phenomena associated with the natural ventilation driving forces of the wind and thermal buoyancy, along with other factors such as climate, building envelope and geometry as well as the occupants. As such, this work utilises dynamic simulations to examine the variation of thermal comfort, in terms of the Predicted Mean Vote (PMV), of a model house equivalent to a size of a typical room under NZ climatic condition and for various operating conditions. To achieve this, it examines the PMV of the room with open and shut windows positions and different airtightness values utilizing coupled thermal and airflow simulations. The results show that there is significant scope for regulating the thermal behaviour and PMV of relatively air-tight natural ventilated residential houses in mild climatic conditions.